2000
DOI: 10.2175/193864700785377979
|View full text |Cite
|
Sign up to set email alerts
|

Regional In-Vessel Composting Facility Relies on Continued Privatization for Improvements

Abstract: In 1986, the Cities of Hickory, Newton, and Conover, together with Catawba County, formed the Hickory Regional Sludge Consortium (HRSC) to develop a regional approach to manage wastewater residuals and septage in North Carolina. The in-vessel composting approach was selected and the Regional Sludge Composting Facility (RSCF) was subsequently constructed, largely funded by a grant from the U.S. Environmental Protection Agency (USEPA). The RSCF began operating in 1990 to process wastewater residuals and septage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…With public acceptance and treatment efficiency in mind, a number of treatment methods and programs have been tried in order to create successful biosolids management programs. Tsang and Treadway (2000) reported that a system approach is crucial to the success of a biosolids processing facility. The system involves dewatering, composting, and curing.…”
mentioning
confidence: 99%
“…With public acceptance and treatment efficiency in mind, a number of treatment methods and programs have been tried in order to create successful biosolids management programs. Tsang and Treadway (2000) reported that a system approach is crucial to the success of a biosolids processing facility. The system involves dewatering, composting, and curing.…”
mentioning
confidence: 99%